Praktik Perjokian Tugas: Dimensi Nilai Kejujuran dan Integritas Perspektif Hukum Islam dan Hukum Positif - Azis Rahman; Muhammad Nur Hidayat; Kurniati Kurniati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The phenomenon of assignment jockeying is a reality of cheating and a bad habit for a student. The practice means paying someone else to complete the assignment of the user. This arises because of the various motives and reasons behind this assignment jockeying action, namely high academic pressure, not understanding or understanding the learning process and the material presented, lack of time, and so on. This research applies the normative theological and juridical approach in answering the issue of the practice of assignment jockeying. Based on this study, it is concluded that the practice of task cheating is contrary to the value of honesty (al-sidq) and integrity. Honesty is the main foundation in studying and interacting in society. Using jockey services means betraying trust, avoiding responsibility, and creating injustice for oneself and others. In addition, this practice also contradicts hifz al-aql (preserving reason) and hifz al-mal (preserving wealth). The education regulatory system in Indonesia is considered contradictory because it ignores the values of honesty, integrity and independence that are the cornerstones of education. The issue is also still being debated due to the weak existing regulations. However, it should be noted that the consequences of the practice will create graduates who are incompetent and unprepared to face challenges in society.